2014
DOI: 10.1128/cvi.00615-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Immunogenicity and Safety of the Conventional Subunit, MF59-Adjuvanted, and Intradermal Influenza Vaccines in the Elderly

Abstract: cThe influenza vaccination is known as the most effective method for preventing influenza infection and its complications in the elderly. Conventional subunit (Agrippal S1; Novartis), MF59-adjuvanted (Fluad; Novartis), and intradermal (IDflu15; Sanofi Pasteur) influenza vaccines are widely used throughout South Korea. However, few comparative studies evaluating the safety and immunogenicity of these vaccines are available. Prior to the beginning of the 2011-2012 influenza season, 335 healthy elderly volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
1
34
0
1
Order By: Relevance
“…The high-dose formulation of influenza vaccination is one example of an attempt to overcome reduced immune function through increased antigen dose. Alternative approaches may rely on the stimulation of specific immune responses; for example, the newly licensed MF59-adjuvanted influenza vaccine demonstrated to have higher immunogenicity and result in longer-lived antibody responses following vaccination (8991). Additional examples include the use of GLA-SE (a TLR4 agonist) leading to increased production of TNFα, IL-6, and IL-12, as well as a Th1 shift in response to influenza challenge (92); or the use of Ov-ASP-1 (a helminth-derived protein adjuvant that stimulates both Th1 and Th2 responses with resulting increases in influenza-specific antibody titer in both young and old mice) (93).…”
Section: Resultsmentioning
confidence: 99%
“…The high-dose formulation of influenza vaccination is one example of an attempt to overcome reduced immune function through increased antigen dose. Alternative approaches may rely on the stimulation of specific immune responses; for example, the newly licensed MF59-adjuvanted influenza vaccine demonstrated to have higher immunogenicity and result in longer-lived antibody responses following vaccination (8991). Additional examples include the use of GLA-SE (a TLR4 agonist) leading to increased production of TNFα, IL-6, and IL-12, as well as a Th1 shift in response to influenza challenge (92); or the use of Ov-ASP-1 (a helminth-derived protein adjuvant that stimulates both Th1 and Th2 responses with resulting increases in influenza-specific antibody titer in both young and old mice) (93).…”
Section: Resultsmentioning
confidence: 99%
“…We will need to further explore the potency of this response to that of common adjuvants and with a mix of target antigens to fully assess the utility of Sbi-III-IV as a universal vaccine adjuvant. For instance, comparison of the action of Sbi-III-IV to the Glaxo-Smith-Kline’s adjuvant systems, particularly AS01 [58], or to MF59 [59] may be of key interest and recent approaches may provide ideal pre-clinical model systems to facilitate this [60, 61] before progression to clinical studies. The work is ongoing but the data herein demonstrate the initial proof of concept.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the PA adjuvant significantly increased the systemic and local antibody titers and the cellular immune response to the ITIV, particularly in the HPA-V group. The HPA-V group nearly fulfilled the immunogenicity evaluation criteria of the Committee for Medical Products for Human Use (seroprotection rate >60%, seroconversion rate >30%, and GMT fold >2) [1], with a seroconversion rate for the A/H3N2 antigen of 40% and fold increases in the HI GMTs for the A/H1N1 and A/H3N2 antigens of 4.04 and 5.90, respectively. Similarly, the mucosal antibody response and the total response were significantly improved in the HPA-V group, particularly for the A/H3N2 antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal influenza is a common acute respiratory viral infection that causes annual epidemics with significant morbidity and mortality in high-risk populations [13]. Vaccine immunization against influenza is the most effective intervention.…”
Section: Introductionmentioning
confidence: 99%